UPAYA HUKUM YANG DAPAT DILAKUKAN KORBAN KECELAKAAN KENDARAAN BERMOTOR TERHADAP PENOLAKAN PEMBERIAN DANA SANTUNAN OLEH PT. JASA RAHARJA (Persero) DI DENPASAR - Sitompul, Rina Florensa; Mudana, I Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2013)
Passenger accident insurance coverage is a mandatory social insurancecompulsory for all passengers who use public vehicles by PT. Jasa Raharja(Persero). This journal using empirical methods in order to know what legalaction can be done in case of denial of victim compensation funds by PT. JasaRaharja (Persero). Attempts to do is to conduct settlement Ex Gratia Et SansPrejudice and Alternative Dispute Resolution.
Keywords: Legal Remedy, Public Vehicles, Refused Compensantions Funds